Factors influencing the behavioral intention to use contactless financial services in the banking industry: An application and extension of UTAUT model - Chen, Lu; Jia, Jing; Wu, Chengzhen (Frontiers in Psychology, 2023)
Contactless financial services are an innovative exploration of the banking industry to integrate digital technology. The purpose of this paper is to figure out factors influencing users’ behavior intention of contactless financial services, in order to promote use behavior, and boost the further development of contactless financial services. In this study, constructed a theoretical model based on extension of unified theory of acceptance and use of technology model and conducted an empirical study using data collected through questionnaires. The structural equation modelling (SEM) method was used to validate the research model. The results reveal that trust and perceived risk are important factors that affect the behavioral intention of contactless financial services; users perceive that contactless financial services have advantages over traditional offline channel, their intention to use contactless financial services will be increased; social influence also has a positive impact on behavioral intention. This paper not only provides a theoretical understanding of contactless financial services use behavior but also offers practical insights to government legislative branches and app developers. By providing personalized services and refining the policies and regulations in the digital environment to promote the development of contactless financial services.